Performance and foulant characteristics of an anaerobic membrane bioreactor treating real textile wastewater. (February 2020) - Yurtsever, Adem; Sahinkaya, Erkan; Çınar, Özer
Graphical abstract: Highlights: Low permeate COD and color concentrations were obtained in the AnMBR. AnMBR was successfully operated at 4.10 LMH with weekly maintenance cleaning. Higher NaOCl concentration in cleaning resulted in lower irrecoverable fouling. Cake layer developed on the membrane retained high molecular organic compounds. Abstract: Treatment and the recovery of textile wastewater are important due to their high volume and toxicity. Although several studies have been conducted on the use of membrane bioreactors (MBR) for textile wastewater treatment, they have mainly focused on synthetic wastewater or aerobic MBRs. However, anaerobic MBR (AnMBR) offers potential advantages of high color removal with lower energy consumption. In this context, this study aims at investigating the performance of AnMBR for the treatment of real textile wastewater. In addition to treatability studies, the membrane foulants were investigated in detail, which may be used in the design and operation of real scale plants. The permeate COD and color concentrations were decreased down to 70 mg/L and 150 Pt-Co, respectively. In the GPC analysis, pollutants with molecular weights greater than 15 kDa detected in the supernatant were removed by the dynamic cake layer developed on the membrane and only low molecular weight organics appeared in the permeate. AnMBR was operated successfully at a flux of 4.1 ± 0.7 LMH with a cleaning cycle of once a week. The impact of physical and chemical cleaning of the fouled membrane on the TMP elevation rate was also evaluated to determine the cleaning efficiency.